Obtenção de nanocompósitos de poliamida 6 / argila nacional com diferentes agentes compatibilizantes - Souza, Michelle Andrade (2005)
The formation of nanocomposites well exfoliated is dependent of several factors, like organic treatment with appropriate ammonium quaternary salts to promote adequate interaction between polymer and clay. The objective of this work was to produce nanocomposites of polymer and brazilian clay through melt intercalation and also to analyze the effects of the clay treatment in satisfactory preparation of the nanocomposite. In this work it were used three different types of salts to obtain organoclay. The nanocomposites of PA6 / organoclay were obtained via melt intercalation method using a corotating twin screw extruder. After extrusion the samples were injection molded into specimens that were tested to obtain the properties of tensile strength, notched izod impact and heat deflection temperature. The thermal behavior of the sample was analyzed by TGA and DSC. The nanocomposites were also characterized by XRD and TEM. The results showed that salt type dodigen affects the mechanical properties of the nanocomposites, HDT and morphology leading to higher level of exfoliation in relation to the others salts. The improvement of the properties was influenced by the level of exfoliation / intercalation obtained wich depends on the processes technique used, surface treatment of the brazilian clays with organic salts and good polar interaction between polymer and clay